2017
DOI: 10.1186/s12889-017-4197-8
|View full text |Cite|
|
Sign up to set email alerts
|

Adaptive goal setting and financial incentives: a 2 × 2 factorial randomized controlled trial to increase adults’ physical activity

Abstract: BackgroundEmerging interventions that rely on and harness variability in behavior to adapt to individual performance over time may outperform interventions that prescribe static goals (e.g., 10,000 steps/day). The purpose of this factorial trial was to compare adaptive vs. static goal setting and immediate vs. delayed, non-contingent financial rewards for increasing free-living physical activity (PA).MethodsA 4-month 2 × 2 factorial randomized controlled trial tested main effects for goal setting (adaptive vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 59 publications
2
93
0
Order By: Relevance
“…Following publication of this article [1], it has come to our attention that in Fig. 5 the top and bottom panels were not presented in the correct order.…”
Section: Erratummentioning
confidence: 99%
“…Following publication of this article [1], it has come to our attention that in Fig. 5 the top and bottom panels were not presented in the correct order.…”
Section: Erratummentioning
confidence: 99%
“…In this study, cash incentives worth about $11 US per week were contingent on reaching a weekly step target of 50,000 steps (a larger reward of $22 US was offered if a 70,000 step target was met). While this study was effective in promoting PA, the authors admit that the cost of the intervention (about $1 to $2 US per person per daymagnitude typically used to promote PA in these types of studies [15,20,[22][23][24][25] was likely too high for most third party payers. Additionally, the effect was not sustained six months after the incentives were discontinued.…”
Section: Introductionmentioning
confidence: 99%
“…According to behavioral economics, timely financial incentives leverage people's predictable tendency to act in favor of their immediate self-interest -a principal referred to as the "present bias" [10]. In the case of PA, the likelihood that someone will be more physically active should increase if a financial incentive is at stake -and the more immediate the incentive the stronger the nudge, according to this theoretical perspective [15].…”
Section: Introductionmentioning
confidence: 99%
“…Personalized step goals are calculated daily for each participant based on the participant's activity over the past nine days employing the moving-window percentile-rank algorithm described by Adams and colleagues [10]. This adaptive goal-setting algorithm sets the daily step goal to the 60 th percentile of the participant's step count distribution of the past nine days meaning that the participant reaches her/his step goal 40% of the times when maintaining her/his recent activity level.…”
Section: The Ally Applicationmentioning
confidence: 99%
“…This adaptive goal-setting algorithm sets the daily step goal to the 60 th percentile of the participant's step count distribution of the past nine days meaning that the participant reaches her/his step goal 40% of the times when maintaining her/his recent activity level. Previous studies demonstrated that this adaptive goal setting outperforms static step goals [10,11]. To facilitate maintenance of behavior change, adaptive step goals are capped at 10,000 steps per day which approximates the WHO recommendations for physical activity [12,13].…”
Section: The Ally Applicationmentioning
confidence: 99%